Sickle cell anemia detection - Albayrak, Batuhan; Darıcı, Muazzez Buket; Kiracı, Furkan; Öğrenci, Arif Selçuk; Özmen, Atilla; Ertez, Kerem (Institute of Electrical and Electronics Engineers Inc., 2018)
Anemia is a common name given to falls in oxygen transport capacity due to some of the functional disadvantages of red blood cells. Pathology Laboratorians put the tissue on the microscope glass and try to diagnose Anemia disease. Processes have been taken for a long time and it has been caused to distract. Therefore it has been caused to misdiagnose the Laboratorian. This work shortens the diagnostic period of the disease and to minimizes error probability of this diagnosis by extracting healthy cells and just having sickle cells on the blood tissue using Image Processing Algorithms with an accuracy of 91.11 %, precision of 92.9 %, recall of 79.05 % for Sickle Cell Anemia.

Anemi, kırmızı kan hücrelerinin bazı fonksiyonel dezavantajları nedeniyle oksijen taşıma kapasitesindeki düşüşlere verilen yaygın bir isimdir. Patoloji Laborantları mikroskop camı üzerine dokuyu yerleştirir ve Anemi hastalığını teşhis etmeye çalışırlar.Bu süreçler uzun sürmektedir ve dikkat dağılmasına neden olmaktadır. Bu nedenle, Laborantların yanlış teşhis etmesine sebep olmaktadır. Bu çalışma %91.11 kesinlik, %92.9 hassasiyet ve %79.05 hatırlanma oranıyla görüntü işleme algortmaları kullanarak kan dokusunda sağlıklı hücreli çıkararak ve sadece orak hücrelere sahip olarak teşhis süresini kısaltır ve teşhisin hata oranını en aza indirir.
Orak hücreli anemi tespiti
Keywords: Circular Hough Transform(CHT); Image Processing; Sickle Cell Anemia; Görüntü İşleme; Dairesel Hough Dönüşümü(DHD); Orak Hücreli Anemi